2023
DOI: 10.1002/fee.2639
|View full text |Cite
|
Sign up to set email alerts
|

Plugging the leaks: antibiotic resistance at human–animal interfaces in low‐resource settings

Maya L Nadimpalli,
Marc Stegger,
Roberto Viau
et al.

Abstract: Antibiotic resistance is one of the greatest public health challenges of our time. International efforts to curb resistance have largely focused on drug development and limiting unnecessary antibiotic use. However, in areas where water, sanitation, and hygiene infrastructure is lacking, we propose that bacterial flow between humans and animals can exacerbate the emergence and spread of resistant pathogens. Here, we describe the consequences of poor environmental controls by comparing mobile resistance elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Detailed analysis of the draft genomes showed that most of the resistance genes ( aadA1 , aadA2 , cmlA1 , dfrA12 and tetA ) were encoded by an MDR cassette located on a single contiguous sequence (contig; Figure 3B). A BLAST search of the contig revealed 99·8% sequence identity to a 21·2 kb region of an 83·2kb plasmid (GenBank accession number CP044301) which had previously been identified in an E. coli isolate obtained from pork in Cambodia 13 .…”
Section: Resultsmentioning
confidence: 97%
“…Detailed analysis of the draft genomes showed that most of the resistance genes ( aadA1 , aadA2 , cmlA1 , dfrA12 and tetA ) were encoded by an MDR cassette located on a single contiguous sequence (contig; Figure 3B). A BLAST search of the contig revealed 99·8% sequence identity to a 21·2 kb region of an 83·2kb plasmid (GenBank accession number CP044301) which had previously been identified in an E. coli isolate obtained from pork in Cambodia 13 .…”
Section: Resultsmentioning
confidence: 97%
“…Despite this progress, tetracyclines are still routinely used in U.S. food animal production, which may explain the high prevalence of tetracycline resistance genes among the FZEC and meat isolates. Further investigations are needed to assess the variability in antimicrobial susceptibility among pediatric FZEC isolates in countries with different antimicrobial policies and practices ( 30 ).…”
Section: Discussionmentioning
confidence: 99%